Poznan Studies in Contemporary Linguistics (De Gruyter Mouton, 2011)
Poznan Studies in Contemporary Linguistics publishes high-quality articles representative of theory-based empirical research in contemporary synchronic linguistics and interdisciplinary studies of language from various perspectives. The journal serves as a forum for modern developments and trends in linguistics, with contributions from the world's leading linguistic labs.